Whey-Bread, an Improved Food Product: Evaluation of Textural Characteristics. Issue 1 (2nd January 2020) - Guiné, Raquel P. F.; Santos, Carina; Rocha, Celeste; Marques, Christelle; Rodrigues, Claudia; Manita, Filipa; Sousa, Filipe; Félix, Márcia; Silva, Sílvia; Rodrigues, Susana
ABSTRACT: The diversity in bread all around the world is enormous and enriched breads are a trend to follow in the next years. The aim of this work was to develop new breads incorporating whey residue, and the final products were analysed for their textural properties, as compared with a basic wheat bread. For measurement of texture two types of teste were used (compression and puncture). The results showed that the whey residue could be used to produce bread with good textural properties, particularly for an improved recipe. The improved whey bread showed good textural characteristics, which remained practically unchanged after 24 h, being this true for the properties evaluated through the compression test (hardness, chewiness, resilience, cohesiveness, springiness) and through the puncture test (external firmness, inner firmness, stickiness, adhesiveness). Finally, very strong correlations were found between cohesiveness and resilience and between adhesiveness and stickiness.